Development of Higher Order Thinking Skills Test based on Revised Bloom Taxonomy - Irfan Hilmi; Nindy Fadlila; Eka Ramadanti; Heri Retnawati; Elly Arliani (Universitas Muhammadiyah Mataram, 2022)
The unequal amount of questions that test students' lower and higher-order thinking skills is a concern in mathematics learning evaluation. The unequal amount of questions resulted in poor cognitive levels among students. The purpose of this study is to develop questions that may be used to assess the higher-order thinking skills of senior high school pupils and fulfill the requirements of being valid, practical, and effective. This study is a developmental research that employs the formative evaluation model. Validation sheets, student evaluation sheets, and examinations that measure students' higher-order thinking skills are among the data gathering procedures employed. According to the researchers' findings, the questions generated matched the valid, practical, and effective requirements. The valid criteria are based on the validators' assessments, and both validators agree that the questions created are good and possible to utilize with a few adjustments. Student answer papers to the established questions serve as the basis for practical criteria. According to the response form, 85 percent of pupils answered positively to the questions. Effective criteria are based on pupils' abilities to answer the questions that have been established. According to the test findings, 85 percent of students satisfied the minimal completeness requirements for both questions testing higher-order thinking skills, indicating that the questions were effective. The questions that have been developed by researchers can be used by teachers to evaluate students' higher-order thinking skills so that teachers do not only provide questions that measure students' lower-order thinking skills. In addition, the questions that have been developed can be used as a reference for developing questions that can measure students' higher-order thinking skills.